Topical Application of Wogonin Provides a Novel Treatment of Knee Osteoarthritis - Smith, Jacob F.; Starr, Evan G.; Goodman, Michael A.; Hanson, Romney B.; Palmer, Trent A.; Woolstenhulme, Jonathan B.; Weyand, Jeffery A.; Marchant, Andrew D.; Bueckers, Shawen L.; Nelson, Tanner K.; Sterling, Matthew T.; Rose, Brandon J.; et al. (Frontiers in Physiology, 2020)
Osteoarthritis (OA) is a degenerative joint disease characterized by inflammatory degradation of articular cartilage and subchondral bone. Wogonin, a compound extracted from the plant Scutellaria baicalensis (colloquially known as skullcap), has previously been shown to have direct anti-inflammatory and antioxidative properties. We examined the pain-reducing, anti-inflammatory, and chondroprotective effects of wogonin when applied as a topical cream. We validated the efficacy of delivering wogonin transdermally in a cream using pig ear skin in a Franz diffusion system. Using a surgical mouse model, we examined the severity and progression of OA with and without the topical application of wogonin. Using a running wheel to track activity, we found that mice with wogonin treatment were statistically more active than mice receiving vehicle treatment. OA progression was analyzed using modified Mankin and OARSI scoring and direct quantification of cyst-like lesions (CLLs) at the chondro-osseus junction; in each instance we observed a statistically significant attenuation of OA severity among mice treated with wogonin compared to the vehicle treatment. Immunohistochemistry revealed a significant decrease in protein expression of transforming growth factor β1 (TGF-β1), high temperature receptor A1 (HTRA1), matrix metalloprotease 13 (MMP-13) and NF-B in wogonin-treated mice, further bolstering the cartilage morphology assessments in the form of a decrease in inflammatory and OA biomarkers.